Optimization of cutting parameters of AISI 316L stainless steel in wet condition during turning operation using the Taguchi technique - Kamble, Pratik; Shrivastava, Ramakant (AIP conference proceedings, 2024)
The response observed when the workpiece is turned using a Computerized Numerical Control (CNC) machine is the main focus of this project. 316L stainless steel, which is frequently used in the food sector, coastal applications, chemical industries, and surgical devices including screws, and orthopedic implants, was selected as the material for the workpiece. A comprehensive analysis has been conducted to investigate the impact of various process variables on MRR, surface roughness, and spindle load. The experimental investigation assessed how the machining of 316L stainless steel material was affected by cutting speed, feed (kept constant for best results), depth of cut, coolant gauge pressure, and coolant jet angle. The L27 orthogonal array (OA) is the subject of the experiment. To examine statistical data, S/N ratio and ANOVA procedures are utilized. The Grey Relational Analysis (GRA) is employed to enhance the output responses. To examine the impact of coolant pressure and angle throughout the operation, the turning process is executed in a flooded environment utilizing the insert coated with TiCN+Al2O3+TiN. It has been determined that the depth of cut exerts a noteworthy influence on the SR, MRR, and spindle load. With equal weights for SR, MRR, and spindle load, the optimal parameters obtained are 1750 rpm (spindle speed), 0.4mm (depth of cut), 0.6 bar (coolant gauge pressure), and 25° (coolant jet angle).